2011
DOI: 10.1149/1.3606487
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Electrochemical Reduction of CO2 in Ionic Liquid EMIMBF3Cl

Abstract: A novel ionic liquid EMIMBF3Cl that contains a BF3Cl− anion has been synthesized. This is the first report of an ionic liquid with a BF3Cl− anion. It was found that CO2 gas can be dissolved and electrochemically reduced at ambient pressure, and room temperature in the ionic liquid EMIMBF3Cl. The reduction of CO2 occurred at a relatively less negative electrode potential of −1.8 V vs. silver wire, compared to previous reported values that are between −2.4 and −2.0 V. The reduction current density can be as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 40 publications
1
50
0
1
Order By: Relevance
“…À1.58 V was observed. Similar to those electrochemical behaviours of CO 2 in organic solvents with quaternary ammonium salts as supporting electrolytes, this irreversible reductive peak observed on Ag electrode can be ascribed to a chemically irreversible, one electron reduction of CO 2 to the radical anion CO 2 .À [13][14][15].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…À1.58 V was observed. Similar to those electrochemical behaviours of CO 2 in organic solvents with quaternary ammonium salts as supporting electrolytes, this irreversible reductive peak observed on Ag electrode can be ascribed to a chemically irreversible, one electron reduction of CO 2 to the radical anion CO 2 .À [13][14][15].…”
Section: Resultssupporting
confidence: 74%
“…Experimental and molecular simulation studies focused on understanding the factors governing the high solubility of CO 2 in imidazoliumbased salts have found that the anion dominates the interactions with the CO 2 , with the cation playing a secondary role [25,26]. Instructed by these findings, many researchers attributed the catalytic effects of imidazolium-based salts towards CO 2 reduction to a Lewis acid-base interaction between CO 2 and anions of the imidazolium-based salts [14,15]. If this assumption is true, CO 2 electroreduction in the presence of an imidazolium-based salt should follow a CE-type mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The ionic conductivity of dry C 2 MIM-BF 3 Cl was 19.0 mS cm À1 at room temperature, and the CO 2 solubility was 0.52 AE 0.25 mass% at 1 atm and room temperature. It was suggested that the anion of C 2 MIM-BF 3 Cl might catalyze CO 2 reduction through an interaction with CO 2 as shown in Fig.…”
Section: 35mentioning
confidence: 95%
“…[6] Snuffin et al have suggested that in the case of a BF 4 À anion it is the boron that can act as a Lewis acid for CO 2 binding [25] by substituting one fluorine for an oxygen bound carbon dioxide molecule. [6] Snuffin et al have suggested that in the case of a BF 4 À anion it is the boron that can act as a Lewis acid for CO 2 binding [25] by substituting one fluorine for an oxygen bound carbon dioxide molecule.…”
Section: Introductionmentioning
confidence: 99%